2006
DOI: 10.1161/01.res.0000235869.50747.e1
|View full text |Cite
|
Sign up to set email alerts
|

Arrhythmogenesis in Catecholaminergic Polymorphic Ventricular Tachycardia

Abstract: Abstract-Catecholaminergic polymorphic ventricular tachycardia (CPVT) is an inherited disease characterized by life threatening arrhythmias and mutations in the gene encoding the ryanodine receptor (RyR2). Disagreement exists on whether (1) RyR2 mutations induce abnormal calcium transients in the absence of adrenergic stimulation; (2) decreased affinity of mutant RyR2 for FKBP12.6 causes CPVT; (3) K201 prevent arrhythmias by normalizing the FKBP12.6-RyR2 binding. We studied ventricular myocytes isolated from w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
236
3
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 283 publications
(256 citation statements)
references
References 23 publications
15
236
3
1
Order By: Relevance
“…38 The explanation is not obvious, but it is important to underline that a latent 'arrhythmogenic propensity', such as reduction of repolarization reserve or destabilization of diastolic potential, often results in arrhythmias only in the presence of physiological triggering factors, such as adrenergic overactivation or stress conditions. 39,40 Moreover, at variance with channelopathies because of mutations, the alterations that we observed in hearts from CO-exposed rats are not permanent, but rather spontaneously normalize toward control during cardiac maturation. To explore the occurrence and/or the susceptibility to develop arrhythmias, further investigation is warranted to assess the effect of stressors on ECG and/or mortality within the 'period of vulnerability'.…”
Section: Limitations Of the Study And Clinical Implicationsmentioning
confidence: 71%
“…38 The explanation is not obvious, but it is important to underline that a latent 'arrhythmogenic propensity', such as reduction of repolarization reserve or destabilization of diastolic potential, often results in arrhythmias only in the presence of physiological triggering factors, such as adrenergic overactivation or stress conditions. 39,40 Moreover, at variance with channelopathies because of mutations, the alterations that we observed in hearts from CO-exposed rats are not permanent, but rather spontaneously normalize toward control during cardiac maturation. To explore the occurrence and/or the susceptibility to develop arrhythmias, further investigation is warranted to assess the effect of stressors on ECG and/or mortality within the 'period of vulnerability'.…”
Section: Limitations Of the Study And Clinical Implicationsmentioning
confidence: 71%
“…The first would be to use an agent that reduces RyR P o and increases SR threshold for Ca 2ϩ waves. Mixed results have been obtained in cellular studies using JTV 519, 40,41 and no clinical study has at present been performed. We have recently shown in cellular studies that decreasing RyR opening with tetracaine can abolish Ca 2ϩ waves and have argued that a more selective version of tetracaine could be clinically useful.…”
Section: Implications For Arrhythmogenesismentioning
confidence: 99%
“…8 This is thought to be responsible for the arrhythmogenic diastolic Ca 2ϩ release in conditions such as digitalis intoxication 6,7,9 and reperfusion following ischemia; 10 and (2) changes in the properties of the RyR. Mutations in the human RyR [11][12][13] or accessory proteins such as calsequestrin 14 increase susceptibility to lethal arrhythmias such as catecholaminergic polymorphic ventricular tachycardia. It has also been suggested that in heart failure, the open probability (P o ) of the normal RyR may be increased by protein kinase A-dependent phosphorylation and that this may be arrhythmogenic.…”
mentioning
confidence: 99%
“…Traditionally, calcium mediated arrhythmogenesis is associated with delayed after depolarizations and abnormal impulse formation. (Katra et al, 2007;Liu et al, 2006;Rosen, 1985;Ter Keurs et al, 2006;Wehrens et al, 2003) However, in this manuscript we focus on how cardiac alternans, a mechanisms of reentrant excitation, is another significant way mechanical dysfunction and arrhythmogenesis are causally related.Cardiac alternans can refer to either mechanical (contractile) or electrical (repolarization) oscillations that occur on an every other beat basis. Cardiac alternans has been recognized for more than 100 years.…”
mentioning
confidence: 99%